IoT Smart Control System: Smoke and Fire Detection Using SIM900A Module - Rahmat Fauzi Siregar; Affandi Affandi; Rohana Rohana; Arya Rudi Nasution; Iqbal Tanjung (Journal of Electrical Technology UMY, 2023)
The main focus of this system is to detect smoke and fire effectively in potential hazard situations. This system utilizes sensor technology to monitor changes in environmental conditions, with the aim of providing quick responses and notifications to users or relevant authorities via a cellular connection. This approach combines feedback signals from sensors and cellular connectivity using the SIM900A module processed with a microcontroller to increase the efficiency and reliability of hazard detection. This system was designed with the aim of providing an efficient and affordable solution for detecting potential fires or other hazardous situations in various environments, including homes, offices and industrial areas. Trial results show that this system is capable of detecting smoke and fire with high accuracy, as well as providing instant notifications via text messages or digital notifications. This innovation is expected to make a positive contribution in improving safety and security in various sectors, while leveraging the potential of IoT connectivity to provide smarter solutions in hazard detection.